(untitled) (Swiss Medical Weekly, 2014)
The purpose of this study was to examine changes in haematopoietic stem cell transplant (HSCT) characteristics and outcome in our combined paediatric and adult programme over the past four decades, since its implementation in 1973. The total number of transplant procedures rose from 109 in the first decade (1973–82) to 939 in the last decade (2003–12). Transplant characteristics changed significantly over time: patient age increased, peripheral blood largely replaced bone marrow as stem cell source, unrelated donors became an alternative to matched siblings, and patients are increasingly transplanted in more advanced disease stages. Advances such as improved supportive care and histocompatibility typing resulted in a steady decrease of transplant-related mortality after allogeneic HSCT (43% in the first decade, 22% in the last decade). Despite this, unadjusted survival rates were stable in the last three decades for allogeneic HSCT (approximately 50% 5–year survival) and in the last two decades for autologous HSCT (approximately 60% 5–year survival). After adjustment for covariates such as donor type, age and stage, the relative risk of treatment failure continuously dropped (for allogeneic HSCT: first decade 1.0, second decade 0.58, third decade 0.51, last decade 0.41). Collectively, these data suggest that improvements in peri- and post-transplant care have allowed considerable extension of transplant indications without having a negative impact on outcome.